I culti politeisti nella Tarda Antichità: osservazioni metodologiche e storiografiche - Dario Cellamare; Francesco Massa (Mythos, 2023)
The article aims to analyze some historiographical and methodological aspects of the study of polytheisms in Late Antiquity. Recent research has somewhat neglected the internal mechanisms of late antique polytheisms. Interpreted simply as residual in an Empire watching the “triumph of Christianity”, studies have continued to project on the polytheistic cults of the fourth and fifth centuries CE the new conception of religion that Christian authors were constructing as an autonomous sphere from the political and social life of the ancient city. Against this backdrop, we focus on some historiographical tendencies that have contributed to the interpretation of late antique polytheisms. Such tendencies include the alleged spread of a soteriological anxiety due to the crises that would have crossed the empire, the individualization of religious practices, the spiritualization of the cult, and the ritualization of philosophical activity. The analysis of the different cases encourages a change of paradigm, which takes into account the plurality of rites, agents, and historical contexts without homologizing them all into an alleged “paganism” that would have eventually been defeated by Christianity.